Kajian Risiko IBPRP dalam Perencanaan Pekerjaan Pengerukan Pemeliharaan Kolam Pelabuhan Ulee Lheue - Ibdayanti, Dinda Rizka; Mubarak, Mubarak; Fatimah, Eldina; Humayra, Siti; Mastura, Cut Annisa Widya Sari; Kesuma, Putra Aulia; Hilal, Iin Shabrina (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
The maintenance dredging work at Ulee Lheue Port aims to maintain optimal water depth for navigation activities. However, this activity involves various risks that must be systematically identified and managed. This study employs the IBPRP (Hazard Identification, Risk Assessment, and Opportunities) method to analyze potential risks in the dredging process.The analysis results indicate four major risks, consisting of two medium-level risks and two high-level risks, with no low-level risks identified. The high-level risks have the potential to significantly impact the stability of the port basin and worker safety. To mitigate these risks, strategies adhering to occupational safety standards and environmental protection measures are implemented, such as the adoption of safer dredging technologies, strict operational supervision, and workforce training.By implementing appropriate risk identification and mitigation measures, the dredging process can be carried out more safely, efficiently, and sustainably. This study is expected to serve as a reference for port management in designing more optimal and risk-based dredging strategies